Effect of potassium fertilization on the postharvest quality of 'Fuji' apples Efeito da adubação potássica na qualidade pós-colheita de maçãs 'Fuji' - Hunsche M. (2003)
The objective of this study was to evaluate the effects of soil K fertilization on fruit mineral composition, quality and storability of 'Fuji' apples. Fruits from a long-term trial that evaluated apple response to annual soil applications of K2O for nine years were harvested in the 1999/2000 growing season and stored in controlled atmosphere (CA) of 1 kPa O2/<0.3 kPa CO2 or 1 kPa O2/2.0 kPa CO 2. Apples were analyzed for quality and ripening parameters at harvest, after eight months of CA storage, and after seven days at 20°C after harvest and after CA storage. The increase on soil K fertilization raised fruit mass, diameter, titratable acidity, red color, and K contents while decreased flesh firmness. There was a significant interaction between K fertilization and storage atmospheres only for internal breakdown: when fruits were stored under 1 kPa O2/<0.3 kPa CO2 no differences were determined between treatments. However, storing apples under 1 kPa O 2/2.0 kPa CO2 resulted in higher breakdown in fruits with lower K concentrations. Fruit weight losses during storage, ground color and rot incidence were not affected by soil K fertilization in the previous nine years.